Guiding intuitive learning in serious games: An achievement-based approach to externalized feedback and assessment - Dunwell, I.; Petridis, P.; Hendrix, M.; Arnab, S.; AL-Smadi, M.; Guetl, Christian (IEEE, 2012)
Despite the rapid emergence of game-based learning as a method for conveying educational content, constructing pedagogies which effectively combine elements of entertainment gaming with methods of instruction remains a demanding task. Through the notion of 'intuitive guided' learning, this paper presents an approach which seeks to facilitate a structured learning experience whilst allowing learners to explore a non-linear environment. To do so, a framework is presented which externalizes the assessment process in a serious game, whilst also providing a means for game content to be adapted dynamically to translate the outcomes of the assessment process to effective feedback. A developed prototype is implemented to examine the theory in practice through the case of a game for civil defence training in schools. Using this prototype, a range of methods in which achievements might be related to learner actions are introduced, and their subsequent implications for intuitive learning discussed. Furthermore, the prototype illustrates how assessment rules can be defined as external to the game and subsequently used to generate feedback for a virtual companion who assumes the role of a more-able partner. The long-term potential of such methods as a source of data on player behaviour is discussed, suggesting further benefits the technique might offer to educators seeking to introduce game based learning within the curriculum in a blended fashion.